2022
DOI: 10.3390/ijms24010037
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of MicroRNA-30c in Neurological Disorders

Abstract: MicroRNAs (miRNAs or miRs) are a class of small non-coding RNAs that negatively regulate the expression of target genes by interacting with 3′ untranslated regions of target mRNAs to induce mRNA degradation and translational repression. The miR-30 family members are involved in the development of many tissues and organs and participate in the pathogenesis of human diseases. As a key member of the miR-30 family, miR-30c has been implicated in neurological disorders such as Alzheimer’s disease, Parkinson’s disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Reduced gene expression was mainly concentrated in pathways associated with nicotine addiction and neuroactive ligand-receptor interaction.. More than 100 different microRNAs (miRNAs) have been detected and identi ed in the bloodstream of people who are in good health. (Kumar and Li 2022). In biology, let-7 is the most studied miRNA, in addition to the let-7, The regulation of differentiation and pluripotency in many animals is largely dependent on the Mir family member.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced gene expression was mainly concentrated in pathways associated with nicotine addiction and neuroactive ligand-receptor interaction.. More than 100 different microRNAs (miRNAs) have been detected and identi ed in the bloodstream of people who are in good health. (Kumar and Li 2022). In biology, let-7 is the most studied miRNA, in addition to the let-7, The regulation of differentiation and pluripotency in many animals is largely dependent on the Mir family member.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison confirmed that the modulated miRNAs were involved in inflammatory and immune pathways ( Supplementary Table S1 ), including relevant upregulated genes such as miR-155-5p and miR-186-5p, which are downregulated in elderly people and those with a neurodegenerative disease ( 26 , 38 ). The upregulation of miR-30c, previously implicated in MS ( 39 ) and characterized in response to pharmacological treatments ( 19 , 40 ), together with the downregulation of miR-199a in the MS relapsing phase is correlated with more frequent Th17 cell differentiation and the severity of the disease ( 41 ). These data suggest a more inflammatory profiling of the patients selected for CLA compared to the pre-OCRE ones, supporting the possible use of miRNAs for a personalized DMT choice.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These diseases encompass various ailments: Parkinson's disease (PD), migraine headache, Alzheimer's disease (AD), multiple sclerosis, seizure disorder, as well as cerebrovascular accidents. 3 NDs can cause slow and progressive deformations, leading to the loss of neurons and synapses. "Protein misfolding" diseases or proteinopathies are now the terms best describing the essential etiologies of NDs and defining these conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 These diseases encompass various ailments: Parkinson's disease (PD), migraine headache, Alzheimer's disease (AD), multiple sclerosis, seizure disorder, as well as cerebrovascular accidents. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation